The Tales of Haw Par Villa - Sze, Bridgel Yi-An (Nanyang Technological University, 2020)
“The Tales of Haw Par Villa” is a video-based installation piece which uses projection mapping to recreate and retell the hidden tales behind certain statues and dioramas of Haw Par Villa (HPV). Intended to be an on-site work which utilises parts of the unique terrain of Haw Par Villa, the work is presented on a makeshift rock which is modelled to mimic the appearance of certain rocky areas of Haw Par Villa.